Are Happier People Less Judgmental of Other People's Selfish Behaviors? Laboratory Evidence from Trust and Gift Exchange Games - Michalis Drouvelis; Nattavudh Powdthavee (Institute for the Study of Labor (IZA), 2013)
What determines people's moral judgments of selfish behaviors? Here we study whether people's normative views in trust and gift exchange games, which underlie many situations of economic and social significance, are themselves functions of positive emotions. We used experimental survey methods to investigate people's moral judgments empirically, and explored whether we could influence subsequent judgments by deliberately making some individuals happier. We found that moral judgments of selfish behaviors in the economic context depend strongly on other people's behaviors, but their relationships are significantly moderated by an increase in happiness for the person making the judgment.
Keywords: C91; 330; happiness; moral judgments; trust games; gift exchange games